(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article discusses some aspects of the development and creation of science-based specialized baby food products based on natural ingredients with balanced recipes. Specialized physiological food components include biological substances for which the properties and norms of daily consumption that are useful for preserving and improving health have been identified and justified. Their effect on the body should be justified by the physiological effect on the biological processes of the body. The most effective and useful components are those of natural origin. These include dry water-soluble extracts of fruits and plants as well as vegetable powders. The article contains a research on the development of the formula composition of fermented milk specialized products for baby food. The use of vegetable raw materials enables the obtainment of compositions with improved vitamin, mineral, carbohydrate and amino acid composition. Specialized baby food products with a combined composition based on animal and vegetable raw materials are most balanced in terms of macro-and micronutrient composition. The results of the research provide opportunities to develop optimal technologies for the production of specialized baby food products in various forms. The paper contains some justifications for the use of advanced components of specialized baby food products based on natural substances and the creation of product forms.